Seroprevalence trends of transfusion transmitted infections among blood donors in a tertiary care hospital of Himachal Pradesh, India - Sachdeva, Amit; Gupta, Anmol; Sharma, Brij; Sharma, Deepak; Sharma, Neetu (International Journal of Research in Medical Sciences, 2016)
Background: Transfusion transmitted infections (TTIs) is a major concern for patients and physicians worldwide. Blood banks in all health care institutions worldwide screen blood for TTIs and ensure that only non-reactive blood is released for clinical use. The present study aimed to study the seroprevalence and trends of transfusion transmitted infections in blood donors in Shimla district of Himachal Pradesh, India. Methods: retrospective review of blood donor’s hospital records (replacement donors and as voluntary donors) covering the period January 2008 to December 2014 was conducted. The serological results for Hepatitis B, Hepatitis C, HIV, syphilis and malaria were retrieved. Results: A total of 39,083 blood donors of both sexes attended the blood bank during this period. Overall, HBC, HIV, syphilis and malaria rate for blood donors was found to be 0.45%. 0.16%, 0.08%, 0.07% and 0.003% respectively. There is a downward trend in sereoprevalence of all screened TTIs namely HBV, HCV, HIV and syphilis and malaria from 2008-2011. Conclusions: The study exhibits that over a period of years there is rise in voluntary blood donations which is heartening and encouraging. Trend analysis for prevalence TTIs among blood donors has shown a decreasing trend. It is recommended that continual quality assured screening of donated blood should be carried out as per the prescribed norms to deal with acquired TTI's.